The value of peripheral perfusion index measurements for early detection of critical cardiac defects - Ozgun Uygur; Ozge Altun Koroglu; Erturk Levent; Merve Tosyali; Mete Akisu; Mehmet Yalaz; Nilgun Kultursay (Pediatrics and Neonatology)
Background: Approximately 25% of congenital heart diseases (CHD) are estimated to be critical and require an intervention. In this study, we aimed to investigate the additional value of peripheral perfusion index (PPI) measurements to pulse oximetry screening for critical CHD (CCHD). Methods: Infants born at Ege University Hospital between May 2013 and September 2015 were prospectively included in the study. In addition to physical examination, pre- and postductal oxygen saturations and PPI values were measured with a new generation pulse oximeter before discharge from the hospital. Results: A total of 3175 newborns (33 with an antenatal diagnosis of CCHD) were included in the study. With the combination of physical examination, pulse oximetry screening and peripheral perfusion index (PPI) measurements, all newborns with CCHD were detected in our study including three infants without an antenatal diagnosis in whom pulse oximetry screening was negative. Conclusion: PPI measurements may be valuable for early detection of obstructive left heart lesions where pulse oximetry screening has limitations in diagnosis. Key Words: congenital heart disease, perfusion index, pulse oximetry, screening